Implementation of Project-Based Learning (PjBL) in Islamic Religious Education to Enhance Vocational High School Students’ Creativity and Academic Achievement in Indragiri Hilir Regency - Leni Sumarni; Muhammad Juni Beddu; Ita Tryas Nur Rochbani (Universitas Hamzanwadi, 2026)
This study examines the implementation of Project-Based Learning (PjBL) in Islamic Religious Education (Pendidikan Agama Islam/PAI) to enhance vocational high school (SMK) students’ creativity and academic achievement in Indragiri Hilir Regency, Indonesia, and maps the enabling and constraining factors affecting its enactment. Employing a descriptive qualitative design, the study involved PAI teachers and students from three schools: SMK Taruna Bhakti Indonesia, SMK Al-Ikhlas, and SMK An-Nur Kuala Selat. Data were collected through classroom observations, semi-structured interviews, and document analysis, and were thematically analyzed through data reduction, data display, and conclusion drawing/verification. The findings indicate that PjBL fosters students’ creativity and learning outcomes when teachers demonstrate strong commitment and pedagogical creativity in adapting projects to each school’s context. Support from school leaders and the local community strengthens a collaborative and religious learning climate. Key challenges include limited instructional time, inadequate facilities, and gaps in teachers’ competencies; however, these constraints can be mitigated by integrating projects into school programs and leveraging local resources. Overall, the study suggests that PjBL in PAI has the potential to improve creativity, academic achievement, and the development of students’ religious and social character.